2023
DOI: 10.1093/cid/ciad484
|View full text |Cite
|
Sign up to set email alerts
|

How We Approach Suppressive Antibiotic Therapy Following Debridement, Antibiotics, and Implant Retention for Prosthetic Joint Infection

Nicolas Cortes-Penfield,
Martin Krsak,
Laura Damioli
et al.

Abstract: The optimal treatment of prosthetic joint infection (PJI) remains uncertain. Patients undergoing debridement and implant retention (DAIR) receive extended antimicrobial treatment, and some experts leave patients at perceived highest risk of relapse on suppressive antibiotic therapy (SAT). In this narrative review, we synthesize the literature concerning the role of SAT to prevent treatment failure following DAIR, attempting to answer three key questions: 1) What factors identify patients at highest risk for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Some experts recommend shared decision making in recommending SAT to patients with factors that are more subjective. These include limited surgical options, recurrent infections, difficult-to-treat pathogens, or immunosuppression [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some experts recommend shared decision making in recommending SAT to patients with factors that are more subjective. These include limited surgical options, recurrent infections, difficult-to-treat pathogens, or immunosuppression [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…While adoption of secondary antibiotic prophylaxis after exchange arthroplasty remains limited, we found that clinicians often use long-term, frequently lifelong, SAT after DAIR or single-stage exchange. This practice, while mentioned as an option in the 2013 IDSA PJI guidelines, is based on limited, methodologically heterogenous, and confounded observational data [ 22 ]. Prolonged antibiotic exposure can lead to adverse events and the emergence of resistant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…These infections can result in further deterioration, delayed healing, heightened pain, and additional complications [ [4] , [5] , [6] ]. Currently, various clinical strategies are employed to treat burn wound infections, including antibiotic treatment [ [7] , [8] , [9] ], surgical interventions [ 10 ], photothermal therapy [ 11 ], as well as the use of wound dressings and coverings. While antibiotic treatment is necessary in certain cases, it is essential to consider its drawbacks and limitations [ 12 ].…”
Section: Introductionmentioning
confidence: 99%